2020
DOI: 10.1161/circresaha.120.317295
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Murine and Human Plaque Proteomics Reveals Pathways of Plaque Rupture

Abstract: Rationale: Plaque rupture is the proximate cause of most myocardial infarctions and many strokes. However, the molecular mechanisms that precipitate plaque rupture are unknown. Objective: By applying proteomic and bioinformatic approaches in mouse models of protease-induced plaque rupture and in ruptured human plaques, we aimed to illuminate biochemical pathways through which proteolysis causes plaque rupture and identify substrates that are cleaved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 106 publications
(127 reference statements)
3
22
1
Order By: Relevance
“…One example would be the production of MMPs, predominantly by macrophages, which can degrade the fibrous cap of atherosclerotic plaques (Amento et al, 1991; Galis et al, 1994; Mach et al, 1997). A recent study conducting parallel proteomic analysis of human and mouse plaques, focusing on the comparison between stable and unstable atherosclerosis, has further strengthened links between proteolytic degradation, inflammation, and the rupture of atherosclerotic plaques (Vaisar et al, 2020). Consequently, an immune cell‐driven bias towards extracellular matrix degradation in atherosclerosis is considered a likely key step in driving plaque instability and rupture.…”
Section: The Need For a Suitable Animal Model Of Plaque Instability A...mentioning
confidence: 99%
See 1 more Smart Citation
“…One example would be the production of MMPs, predominantly by macrophages, which can degrade the fibrous cap of atherosclerotic plaques (Amento et al, 1991; Galis et al, 1994; Mach et al, 1997). A recent study conducting parallel proteomic analysis of human and mouse plaques, focusing on the comparison between stable and unstable atherosclerosis, has further strengthened links between proteolytic degradation, inflammation, and the rupture of atherosclerotic plaques (Vaisar et al, 2020). Consequently, an immune cell‐driven bias towards extracellular matrix degradation in atherosclerosis is considered a likely key step in driving plaque instability and rupture.…”
Section: The Need For a Suitable Animal Model Of Plaque Instability A...mentioning
confidence: 99%
“…Therefore, the ability to model plaque instability and rupture in animals is a critically required tool for cardiovascular research to allow for the discovery and dissection of the fundamental biological mechanisms underpinning cardiovascular events. Indeed, transcriptomic and proteomic comparisons between the regions displaying stable and unstable atherosclerosis indicate that both are different disease entities (Chen et al, 2013; Vaisar et al, 2020). With this in mind, we will now discuss the TS model, which our laboratory designed and validated to provide a reliable, flexible, and widely applicable model of plaque instability and rupture.…”
Section: The Need For a Suitable Animal Model Of Plaque Instability A...mentioning
confidence: 99%
“…Replicating the observed DBD kidney key degradation profiles of talin-1 in human kidney immortalized podocyte cells revealed a role of the calpain-1-TGFβ axis in proteolytic activation and cytoskeletal dysregulation that may deem grafts susceptible to subsequent injury-a causal link that further studies should aim to establish.To investigate the donor kidney degradome we analyzed deceased and living donor kidney biopsies obtained with identical procurement protocols to minimize preanalytical confounding factors. This stringent experimental selection, based on paired transplant outcomes, also increased our confidence in obtaining meaningful data that predominantly relates to donor minimizing the impact or bias from surgical or posttransplant factors.We, and more recently others, have shown that the application of the PROTOMAP technique to complex clinical samples provides a comprehensive profiling of both N-and C-terminal proteoforms with sufficient sequence coverage to determine epitope coverage by commercial antibodies, thereby allowing validation by immunoblotting 25,41,42. Initial, unbiased PROTOMAP degradation profiling and pathway analysis mapped α -actinin, synaptopodin, talin, laminin β2, integrin α1, and utrophin as a cluster of cytoskeletal proteins associated with focal adhesion in podocytes had undergone enhanced proteolytic processing in DBD kidneys with SO posttransplant function.…”
mentioning
confidence: 99%
“…We, and more recently others, have shown that the application of the PROTOMAP technique to complex clinical samples provides a comprehensive profiling of both N-and C-terminal proteoforms with sufficient sequence coverage to determine epitope coverage by commercial antibodies, thereby allowing validation by immunoblotting. 27,47,48 . Initial, unbiased PROTOMAP degradation profiling and pathway analysis mapped α -actinin, Synaptopodin, Talin, Laminin β2, Integrin α1 and Utrophin as a cluster of cytoskeletal proteins associated with focal adhesion in podocytes had undergone enhanced proteolytic processing in DBD kidneys with SO posttransplant function.…”
Section: Discussionmentioning
confidence: 99%